Prescription Pattern of Antibiotics in Paediatric Patients in a Rural Teaching Hospital of North India - Malik, Ankush; Nain , Parminder; Maini, Baljeet; Shsihpal,; Kaur, Jaspreet (Journal of Nepal Paediatric Society, 2021)
Introduction: Due to complex dosage calculations, requirement and different pharmacokinetics profile of drugs in paediatric population, there is a risk of development of drug resistance due to the excessive and inappropriate use of antibiotics. The aim of this study is to determine the antibiotic prescriptions pattern and analyse the rationale use of antibiotic in paediatric patient. Methods: A prospective observational study was carried out for the period of six months. Data was obtained from the records of paediatric patients between six months to 12 years of age who visited the hospital for febrile illnesses. Appropriateness of the prescriptions was evaluated by considering various parameters like selection of antibiotics (adherence to standard treatment protocols of childhood febrile illnesses), dose, dosage form, route, frequency and duration of antibiotic administration. Quantitative data was analysed in terms of percentage and graphs. Results: One hundred and fifty prescriptions in a successive manner from paediatric department were collected and analysed, out of which 40% were male & 60% were female cases. The mean age of the patients was 5.9 ± 3.3 years. The range of duration of antimicrobial therapy was 3 - 9 days (6.03 ± 3.53 days). Sixty six percent of paediatric patients were on single antibiotic and most of the paediatric patients were receiving parenteral preparation. The antibiotic treatment was given on the basis of definitive diagnosis in 52% and empirical therapy in 46% cases. Antibiotic prescribed were from class cephalosporin (80%) followed by penicillin (18%) and microcline (14%), glycopeptides (2%) and nitroimidazoles (2%). Conclusions: Febrile children received antibiotics on an empirical basis, in accordance with standard treatment protocols. Cephalosporins are the major class of drugs prescribed.